Regenerative Medicine and Angiogenesis; Focused on Cardiovascular Disease - Seyed Zachariah Moradi; Faramarz Jalili; Zohreh Hoseinkhani; Kamran Mansouri (Tabriz University of Medical Sciences, 2022)
Cardiovascular disease (CVD) is a major concern for health with high mortality rates around the world. CVD is often associated with partial or full occlusion of the blood vessel network. Changes in lifestyle can be useful for management early-stage disease but in the advanced stage, surgical interventions or pharmacological are needed to increase the blood flow through the affected tissue or to reduce the energy requirements. Regeneration medicine is a new science that has provided many different options for treating various diseases, especially in CVD over the years. Stem cell therapy, gene therapy, and tissue engineering are some of the powerful branches of the field that have given patients great hope in improving their condition. In this review, we attempted to examine the beneficial effects, challenges, and contradictory effects of angiogenesis in vivo, and in vitro models' studies of CVD. We hope that this information will be able to help other researchers to design new effective structures and open new avenues for the treatment of CVD with the help of angiogenesis and regeneration medicine in the future.